Detection and molecular characterization of Livestock‐Associated MRSA in raw meat on retail sale in North West England. (1st March 2017) - Fox, A.; Pichon, B.; Wilkinson, H.; Doumith, M.; Hill, R.L.R.; McLauchlin, J.; Kearns, A.M.
Abstract: Limited data are available on the prevalence of livestock‐associated methicillin‐resistant Staphylococcus aureus (LA‐MRSA) in the UK. We tested 124 raw meat samples for MRSA including pork ( n = 63), chicken ( n = 50) and turkey ( n = 11) collected from retail outlets in North West England between March and July 2015. MRSA was recovered from nine (7·3%) samples (four chicken, three pork and two turkey) from different butchers and supermarkets. Four were labelled of UK origin, three were from continental Europe; the origin was not specified for two samples. Whole‐genome sequencing (WGS), spa typing and the presence of lineage‐specific canonical single nucleotide polymorphisms confirmed that they belonged to the livestock‐associated clade of clonal complex (CC) 398. Seven (77·8%) isolates were multi‐drug resistant. Phylogenetic analyses showed the isolates were diverse, suggesting multiple silent introductions of LA‐MRSA into the UK food chain. Two chicken meat isolates belonged to a sub‐clade recently reported from human cases in Europe where poultry meat was the probable source. The low levels of MRSA identified (<20 CFU per g) and absence of enterotoxin genes suggest the risk of acquisition of, or food‐poisoning due to, LA‐MRSA is low. Nevertheless, the MRSA contamination rate is higher than previously estimated; further evaluation of the public health impacts of LA‐MRSA is warranted. Significance and Impact of the Study: Livestock‐associated methicillin‐resistant Staphylococcus aureus (LA‐MRSA) is a public health concern worldwide, but has only been reported sporadically in the UK. In the largest UK study to date, samples of raw meat at retail sale were examined for both the presence and levels of MRSA. We report the first isolations of CC398 LA‐MRSA from poultry meat in the UK including representatives of a particular sub‐clade associated with cases of human infection/colonization in Europe. Although levels were low (<20 CFU per g), the contamination rate was higher than previous UK studies. Moreover, whole‐genome sequencing revealed multiple independent introductions of LA‐MRSA into the UK food chain.